Folding kinetics of G-quadruplexes : duplex stem loops drive and accelerate G-quadruplex folding - Nguyen, Thi Quynh Ngoc (2021)
The folding kinetics is an important parameter affecting the relevance of DNA and RNA G-quadruplex (G4) structures in biological processes. Previous studies of the G4 folding kinetics mainly depended on fast measurement techniques. In previously available examples of G4s with loops up to three residues, the folding kinetics spanning several orders of magnitude has been reported, ranging from milliseconds to over 100 s. It is difficult to systematically and fundamentally understand the effect of multiple parameters, especially the loop properties, on the G4 folding kinetics, as the G4 fold is often altered when the sequence is varied. In this study, judicious choices of multiple parameters allowed us to bring various systems into the measurable window of a simple UV absorption technique. Using a well-controlled parallel-stranded G4 fold, we were able to systematically investigate the effect of seven different parameters of the environment and loop properties (temperature, K+ concentration, ionic strength, co-solute, loop length, loop sequence, and loop structure) on the G4 folding kinetics. We found that structured loops can drive up the G4 folding: for a long loop, the fast folding of a stem loop can guide the G4 folding and accelerate its folding kinetics by several orders of magnitude compared to an unstructured loop counterpart.